Patients' satisfaction with psychiatric nursing care in Benin, Nigeria - Faith R. Omoronyia; Akon E. Ndiok; Kingsley O. Enang; Elizabeth I. Obande (Elsevier, 2021)
In many low-middle income countries including Nigeria, shortage of psychiatric nurses and adverse working conditions, potentially impairs quality of nursing care provided. Quality of care may influence uptake of available mental health care services. This study was aimed at assessing level of psychiatric patients' satisfaction with nursing care in one of two public mental health hospitals in South-South Nigeria. Study design was cross-sectional descriptive, with use of simple random sampling technique to recruit patients from Federal Neuropsychiatric Hospital, Benin, Edo State, Nigeria. Data analysis was done using SPSS version 21, with chi-square as inferential statistic, and p-value set at 0.05. One hundred and eighty-five (185) respondents were surveyed, with mean age of 36.3 ± 10.1 years. Common psychiatric diagnoses were schizophrenia (40.0%) and depression (34.1%). Mean satisfaction was 3.53 ± 0.69 ranging from 1.6 to 5.0. There was 52.4% prevalence of satisfaction and 47.6% prevalence of dissatisfaction with nursing care provided. Common areas of dissatisfaction were privacy nurses gave (61.1%), nurses' willingness to respond to subjects' needs (55.7%), and nurses' awareness of subject's needs (55.1%). Common areas of satisfaction were nurses putting relatives' mind to rest (61.6%), nurses' capability at their job (60.5%). Dissatisfaction was significantly commoner among males and those diagnosed with depression and bipolar affective disorder (p < 0.05). This study identified key areas of dissatisfaction and satisfaction with mental health nursing services in a low-middle-income country setting. Psychiatric nurses need to be aware of these areas, towards optimization of mental healthcare provision peculiar to their settings.